Optimizing Information and Communication Technology (ICT) to Build Competitive Advantage for Batik Craftsmen - Zuhri, Fahmi Muhammad Az; Sukma, Erlangga Andi; Nikmah, Farika; Rahmawati, Rizka (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2024)
ICT implementation is the application of information technology carried out in business to improve performance, maintain sustainability and gain competitive advantage. ICT implementation in this study is ICT infrastructure, ICT management and ICT proactive. ICT implementation in this study emphasizes the commitment to invest in information technology software and hardware. Then synergize ICT with its business processes. This study uses a quantitative approach, with a sample of 280 batik craftsmen in East Java, Indonesia. Data were obtained by distributing questionnaires, and 264 questionnaires were returned and considered suitable for use as research data. Data were analyzed statistically with SEM PLS. The independent variables in this study are ICT infrastructure, ICT management, ICT proactive and ICT implementation and the dependent variable is competitive advantage. The results of the study found that there was a positive and strong relationship, both for direct and indirect relationships. ICT implementation provides positive and significant support as a moderator in the relationship between ICT infrastructure, ICT management, ICT proactive and competitive advantage. ICT implementation also has a positive and significant direct effect on competitive advantage. ICT is currently not only considered, but should be implemented for batik craftsmen for competitive advantage.